Nonlinear in-plane instability of functionally graded multilayer graphene reinforced composite shallow arches. (15th November 2018) - Yang, Zhicheng; Yang, Jie; Liu, Airong; Fu, Jiyang
Abstract: This paper investigates the in-plane instability of functionally graded multilayer composite shallow arches reinforced with a low content of graphene platelets (GPLs) under a central point load. The GPL weight fraction, which is a constant within each individual GPL reinforced composite (GPLRC) layer, follows a layer-wise variation along the thickness direction. The effective Young' modulus of the GPLRC is estimated by modified Halpin-Tsai micromechanics model. The virtual work principle is used to establish the nonlinear equilibrium equations for the FG-GPLRC arch fixed or pinned at both ends which are then solved analytically. A parametric study is conducted to examine the effects of distribution pattern, weight fraction, and size of GPL nanofillers and the geometrical parameters of the FG-GPLRC arch on its buckling and postbuckling behaviors. The conditions for multiple limit point buckling to occur in an FG-GPLRC pinned arch are also discussed. It is found that GPL nanofillers have a remarkable reinforcing effect on buckling and postbuckling performances of nanocomposite shallow arches.